2012
DOI: 10.1212/wnl.0b013e31826357a5
|View full text |Cite
|
Sign up to set email alerts
|

Focal atrophy on MRI and neuropathologic classification of dementia with Lewy bodies

Abstract: Objective: To determine the association between the focal atrophy measures on antemortem MRI and postmortem neuropathologic classification of dementia with Lewy bodies (DLB) using the Third Report of the DLB Consortium criteria. Methods:We retrospectively identified 56 subjects who underwent antemortem MRI and had Lewy body (LB) pathology at autopsy. Subjects were pathologically classified as high (n ϭ 25), intermediate (n ϭ 22), and low likelihood DLB (n ϭ 9) according to the Third Report of the DLB Consortiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
75
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 41 publications
12
75
1
Order By: Relevance
“…Hippocampal AD pathology is also a feature of DLB, as previous imaging studies have consistently demonstrated that the level of hippocampal atrophy observed in DLB is less than in AD (Hashimoto et al, 1998; Tam et al, 2005; Burton et al, 2009; Watson et al, 2012), and the level of atrophy relates to concurrent AD pathology measured post mortem (Burton et al, 2009; Kantarci et al, 2012). The extent of the atrophy may also influence the subsequent clinical course of DLB, as individuals with higher levels of hippocampal atrophy have a shorter survival time compared with those with lower levels of atrophy (Graff‐Radford et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…Hippocampal AD pathology is also a feature of DLB, as previous imaging studies have consistently demonstrated that the level of hippocampal atrophy observed in DLB is less than in AD (Hashimoto et al, 1998; Tam et al, 2005; Burton et al, 2009; Watson et al, 2012), and the level of atrophy relates to concurrent AD pathology measured post mortem (Burton et al, 2009; Kantarci et al, 2012). The extent of the atrophy may also influence the subsequent clinical course of DLB, as individuals with higher levels of hippocampal atrophy have a shorter survival time compared with those with lower levels of atrophy (Graff‐Radford et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…In several studies, patients with probable DLB showed an Alzheimer's diseaselike pattern of atrophy (Whitwell et al, 2007b;Sabattoli et al, 2008;Zhong et al, 2014) while autopsy confirmation later showed that the presence of tau neurofibrillary tangles and their Braak stage (Braak and Braak, 1991) of Alzheimer's disease primarily explained the cross-sectional (Burton et al, 2009;Kantarci et al, 2012a;Murray et al, 2013) and longitudinal (Nedelska et al, 2015) atrophy observed in the medial temporal structures.…”
Section: Introductionmentioning
confidence: 99%
“…5 Hippocampal volumes on antemortem MRI are preserved in patients with DLB who have little or no additional AD pathology at autopsy. [6][7][8] Hippocampal volumes are lower in patients with DLB with increasing Braak neurofibrillary tangle stage regardless of the severity of Lewy body disease pathology. 7 Furthermore, while hippocampal phospho-tau burden is associated with hippocampal atrophy, a-synuclein burden does not appear to influence the global hippocampal volume in patients with Lewy body pathology.…”
mentioning
confidence: 99%
“…[6][7][8] Hippocampal volumes are lower in patients with DLB with increasing Braak neurofibrillary tangle stage regardless of the severity of Lewy body disease pathology. 7 Furthermore, while hippocampal phospho-tau burden is associated with hippocampal atrophy, a-synuclein burden does not appear to influence the global hippocampal volume in patients with Lewy body pathology. 9 Therefore preserved hippocampal volumes may predict progression to DLB vs AD in MCI.…”
mentioning
confidence: 99%
See 1 more Smart Citation